The lower well-being of young Australian adults with self-reported disability reflects their poorer living conditions rather than health issues - Kariuki, M; Honey, A; Llewellyn, G; Emerson, Eric (My University, 2012)
Objective: To determine the extent to which the lower well-being of young Australians with disabilities could be accounted for by increased rates of exposure to adversity and reduced access to personal, economic, social and community resources. Methods: Secondary analysis of data extracted from Waves 1 (2001) to 8 (2008) of the annual longitudinal survey of Household Income and Labour Dynamics in Australia. Results: Self-reported disability was associated with significantly lower scores on all indicators of psychological well-being. However, people self-reporting disability were more likely to be exposed to adversity and less likely to have access to a range of personal, economic, material, social and community resources. When these between-group differences in social context were controlled for, the between-group differences in psychological well-being were largely eliminated. Conclusion: Our results suggest that, among younger adults in Australia, the association between disability and lower psychological well-being largely reflects their increased risk of exposure to adversity and reduced access to resources, rather than the presence of health conditions or impairments per se. Implications: Public health interventions aimed at improving the well-being of young adults with a disability need to address the predominantly social determinants of well-being in this group.
Australian and New Zealand Journal of Public Health
Keywords: Disability & Carers; Families and relationships; Disability & Carers; Families and relationships